Effectiveness of mathematical education - Biernacki, Marek (Skuteczność edukacji matematycznej, 2009)
In the paper, the measure of teaching quality is introduced. This measure de-pends on distribution and average level of students' knowledge. It has been applied and verified on the basis of the data concerning first-year students of the Wrocław University of Economics (results of secondary school certificate in mathematics, exam in mathematics at the University and the survey conducted at the end of the course in mathematics have been taken into account). Results for Poland, concerning effectiveness and efficiency of teach-ing, have been compared to other countries
Didactics of Mathematics, 2009, Nr 5-6 (9-10), s. 19-32
Keywords: measurement; effectiveness and efficiency of teaching